2015
DOI: 10.1038/ncomms9137
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial uncoupling links lipid catabolism to Akt inhibition and resistance to tumorigenesis

Abstract: In order to support growth, tumor cells reprogram their metabolism to simultaneously up-regulate macromolecular biosynthesis while maintaining energy production. Uncoupling proteins (UCPs) oppose this phenotype by inducing futile mitochondrial respiration that is uncoupled from ATP synthesis, resulting in nutrient wasting. Here, using a UCP3 transgene targeted to the basal epidermis, we show that forced mitochondrial uncoupling inhibits skin carcinogenesis by blocking Akt activation. Similarly, Akt activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…In another study, the overexpression of uncoupling protein 3, a close family member of UCP1, reduced the growth of skin cancer in mice as a result of constitutive oxidation of substrates and nutrients that are essential for maintaining tumour growth, without simultaneous ATP production . Furthermore, mitochondrial uncoupling blocked the activation of AKT serine/threonine kinase 1 (AKT) in mice thereby limiting proliferation and tumorigenesis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, the overexpression of uncoupling protein 3, a close family member of UCP1, reduced the growth of skin cancer in mice as a result of constitutive oxidation of substrates and nutrients that are essential for maintaining tumour growth, without simultaneous ATP production . Furthermore, mitochondrial uncoupling blocked the activation of AKT serine/threonine kinase 1 (AKT) in mice thereby limiting proliferation and tumorigenesis .…”
Section: Discussionmentioning
confidence: 99%
“…38 In another study, the overexpression of uncoupling protein 3, a close family member of UCP1, reduced the growth of skin cancer in mice as a result of constitutive oxidation of substrates and nutrients that are essential for maintaining tumour growth, without simultaneous ATP production. 39 Furthermore, mitochondrial uncoupling blocked the activation of AKT serine/ threonine kinase 1 (AKT) in mice thereby limiting proliferation and tumorigenesis. 39 Therefore, UCP1 could inhibit tumour growth by modulating and disrupting the metabolism of mitochondrion, which would lead to loss of nutrients, catabolism, disturbance of the cellular membrane and AKT inhibition (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• NO further reacts with O 2 •− to form ONOO − which inhibits all mitochondrial complexes (24). There is some evidence from small animal models that cyclosporine treatment might prevent assembly of the mPTP, although a larger meta-analysis failed to show any significant effect (25).…”
Section: Mitochondrial Enzymatic Chain Disruptionmentioning
confidence: 99%
“…3 In a recent publication, we showed that the mechanism of cancer prevention in K5-Ucp3 mice occurs through a novel mechanism of metabolic regulation of thymoma viral proto-oncogene 1 (protein kinase B, best known as Akt1) signaling. 4 To narrow down the possible mechanisms by which Ucp3 overexpression might antagonize tumorigenesis, our first step was to distinguish between effects on tumor initiation and tumor promotion. We bred K5-Ucp3 mice with the "pre-initiated" Tg.AC mouse strain, a transgenic strain that harbors an oncogenic mutation in the Harvey rat sarcoma virus oncogene (Hras), 5 and found that K5-Ucp3/Tg.AC mice are still dramatically protected from tumor formation, leading us to focus on the effect(s) of Ucp3 overexpression on tumor promotion.…”
mentioning
confidence: 99%